-24=-12+3t

Simple and best practice solution for -24=-12+3t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -24=-12+3t equation:


Simplifying
-24 = -12 + 3t

Solving
-24 = -12 + 3t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-3t' to each side of the equation.
-24 + -3t = -12 + 3t + -3t

Combine like terms: 3t + -3t = 0
-24 + -3t = -12 + 0
-24 + -3t = -12

Add '24' to each side of the equation.
-24 + 24 + -3t = -12 + 24

Combine like terms: -24 + 24 = 0
0 + -3t = -12 + 24
-3t = -12 + 24

Combine like terms: -12 + 24 = 12
-3t = 12

Divide each side by '-3'.
t = -4

Simplifying
t = -4

See similar equations:

| 9x-10=7x-4 | | -x-3(x-2)=4(2-3x)-2x | | -3(6y-3)-y=-3(y-3) | | -(4x-5)-(4x-6)+8=-7(x-1)-(5x+7)+3 | | 4x-10+6x-40=180 | | x-2=15+8-9x | | 5x+2=2(2x+3) | | 1.5x-2=2(-x+1) | | -5x=11+4x | | graphy=x^2-x | | 4x-9-7x=-7x-11+3x | | u^2-9= | | 7x-9x+2=x-6+8 | | x-2=15x+8 | | 49w^2+56w+16= | | 3y^2+32y+20= | | 4z+9-2z=33-2z | | 4(x-7)=3(2x-1)+3 | | 5x-44=-8 | | 21x^2+19x-2= | | 22+9x=-12+8x | | 6u^2+48u+72= | | 7p+-3p=-4p+16 | | x=6-25 | | 15-4x=9-5x | | -10x=190 | | 7+2x=x+8 | | 8(-3v-7)=20-5v | | x=1/2(0+28.5)7 | | 1(4x+2)=4x-12(x-1) | | 4x+2=4+3x | | 1.2(5x-4)=3.6x-12(x+1) |

Equations solver categories